2020
DOI: 10.1111/cas.14336
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin‐induced programmed cell death ligand‐2 expression is associated with metastasis ability in oral squamous cell carcinoma

Abstract: Programmed cell death ligands (PD-Ls) are expressed in tumor cells where they bind to programmed cell death-1, an immunocyte co-receptor, resulting in tumor cell evasion from the immune system. Chemotherapeutic drugs have been recently reported to induce the expression of PD-L, such as PD-L1, in some cancer cells. However, little is known regarding PD-L2 expression and its role in oral squamous cell carcinoma (OSCC). In this study, we examined the effect of cisplatin on the expression and regulation of PD-L2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The EGFR and JAK/STAT pathways have been reported to play a crucial role in the regulation of PD‐L1/L2 expression, and several studies have shown that these pathways are influenced by CDDP or 5‐FU treatment. 14 , 15 , 24 , 25 Thus, we examined EGFR and JAK/STAT pathway proteins in cell lines with decreased PD‐L2 in response to CDDP (TE‐1 and TE‐10) and those with increased PD‐L2 in response to CDDP (TE‐9 and KYSE30; Figure 3A ). We found that pSTAT1/3 was decreased in TE‐1 and TE‐10 cells treated with CDDP, while pSTAT1/3 was increased in TE‐9 and KYSE30 cells incubated with CDDP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGFR and JAK/STAT pathways have been reported to play a crucial role in the regulation of PD‐L1/L2 expression, and several studies have shown that these pathways are influenced by CDDP or 5‐FU treatment. 14 , 15 , 24 , 25 Thus, we examined EGFR and JAK/STAT pathway proteins in cell lines with decreased PD‐L2 in response to CDDP (TE‐1 and TE‐10) and those with increased PD‐L2 in response to CDDP (TE‐9 and KYSE30; Figure 3A ). We found that pSTAT1/3 was decreased in TE‐1 and TE‐10 cells treated with CDDP, while pSTAT1/3 was increased in TE‐9 and KYSE30 cells incubated with CDDP.…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 12 , 13 In contrast, only a few reports have examined the effect of these treatments on PD‐L2. 14 , 15 Given the efforts to develop combination treatments of ICIs with conventional chemotherapeutic drugs, 16 , 17 , 18 clarifying the change of PD‐L1/L2 expression in response to chemotherapy is clinically important.…”
Section: Introductionmentioning
confidence: 99%
“…Sudo, et al established a cisplatin-resistant OSCC cell line, HSC-2, and found that cisplatin upregulated the gene expression levels of PD-L2, ABCG2 in HSC-2 in a time-dependent manner. In addition, STAT1/3 mediated the induction of PD-L2 by cisplatin, and PD-L2-positive cells have higher metastatic and invasive potential compared to PD-L2-negative cells (97). These studies suggested that anti-PD-L immunotherapy may be valuable for cisplatin-resistant OSCC patients.…”
Section: Immune Microenvironmentmentioning
confidence: 90%
“…There are also research reports showing increased PD-L1 expression with platinum treatment in other tumours [ 36 , 37 ]. Sudo et al reported that cisplatin also increased PD-L2 expression in oral squamous cell carcinoma cell lines [ 38 ]. However, no significant change in PD-L1 expression was observed in the chemosensitive cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%